Dual mediating effects of marital satisfaction and family decision-making power on the relationship between self-disclosure and depressive symptoms in IVF-ET/ICSI-ET patients: a cross-sectional study - Jia, Yuedi; Wang, Jieyu; Xu, Qianhua; Luo, Guiying; Chen, Ren; Wang, Danni (Frontiers in Psychiatry, 2025)
ObjectiveInfertility has become one of the major public health problems, and assisted reproductive technology is the main treatment. Depressive symptoms are one of the most common mental illnesses treated with this technology. The aim of this study was to investigate the effects of partner self-disclosure, marital satisfaction and family decision-making power on depressive symptoms in assisted reproductive therapy patients.MethodsA cross-sectional survey of self-disclosure, marital satisfaction, family decision-making power and depressive symptoms was performed in 1076 patients who underwent IVF/ICSI-ET treatment at the Reproductive Medicine Centre of the First Affiliated Hospital of Anhui Medical University.Results(1) Age and power base were the influencing factors of depressive symptoms. (2) The results of mediation effect test showed that marital satisfaction had a significant suppressing effect on depressive symptoms in assisted reproductive therapy patients, accounting for 30.05% of the total effect; family decision-making power had a significant partial mediating effect on depressive symptoms in assisted reproductive therapy patients, accounting for 28.81% of the total effect.ConclusionMarital satisfaction and family decision-making power play a partial mediating role between self-disclosure and depressive symptoms. The score of marital satisfaction helps to reduce depressive symptoms, but the increase of family decision-making power predicts the increase of depressive symptoms. In addition, the results highlight gender differences in marital satisfaction and family decision-making power and the complexity of family relationships.